Access to Fluorescent Azines from N‐Heterocyclic Carbene Precursors and N‐Tosylhydrazones. Issue 11 (28th April 2017) - Wei, Siping; Li, Shuangxun; Chen, Changyou; He, Zhonghong; Du, Xi; Wang, Li; Zhang, Chun; Wang, Qin; Pu, Lin
Abstract: An efficient synthesis of azines from the reaction of N‐heterocyclic carbene precursors with N ‐tosylhydrazones has been developed. This method avoids the direct use of diazo compounds and allows the synthesis of structurally diverse azines. An azine was further found to exhibit strong yellow fluorescence and shows promise as a reagent for biological imaging. Abstract :